Pengendalian Penyakit Pustul Xanthomonas axonopodis pv. glycines Pada Kedelai Dengan Bacillus spp. Asal Filosfer Gulma di Pertanaman Kedelai - Siti Rahayu; Suhartiningsih Dwi Nurcahyanti (Fakultas Pertanian Universitas Jember, 2019)
Soybean pustule disease by Xanthomonas axonopodis pv. glycines (Xag) is one of the important diseases of soybean plant. Application Bacillus spp. origin of weed phyllosphere has a great potential as an alternative to control because it is isolated to origin of same region as Xag is the phyllosphere. Research by Nurcahyanti and Ayu obtained the best five isolates of Bacillus spp. of weeds phyllosphere in soybean cropping in inhibiting Xag in vitro. This study used the complete random draft (RAL) 6 treatment, 4 repeats, each unit consists of 4 plants wich treatment application of 5 isolates of Bacillus spp. namely K = control; A = Bacillus JG 1.3; B = Bacillus JG 3.6; C = Bacillus JG 1.4.1; D = Bacillus BGd 1.1; E = Bacillus Bp 2.2. The results showed that application of Bacillus spp. could inhibit Xag in vitro with bacteriostatic mechanism and isolates Bacillus BGd 1.1 has the greatest inhibition of 14.25 mm. Fifth Bacillus spp. can suppress the development of disease and isolates Bacillus BGd 1.1 has best results with the incubation period during 13 HSI, the severity of disease 10.07%, infection rate 0.045 unit/day as well as the effectiveness of control 85.72%. The fifth isolates of Bacillus spp. can not increase the number of leaves but can increase number of branches and isolates Bacillus JG 1.3, Bacillus JG 1.4.1 and Bacillus BGd 1.1 can increase the height of soybean crop.